Much More than a Metaphor: Translation in Anthropology - Sora, Gustavo Alejandro (2021)
During the 1990s, theories of globalization spread as rapidly as neoliberalism. Their effects are widely recognized and continue to have a major influence on broad sectors of the social sciences and the humanities. These include attacks on scientific thought in the rationalist-universalist tradition and the proclamation of a New Era, recognizable in discourse distinguished by the use of the prefixes “pluri-,” “trans-” and “post-,” the use of neologisms, generally to demonstrate the increasing uniformity of human experiences, and a fascination with the metaphorical. If the Globish alluded to by Barbara Cassin in the epigraph is a sign of the new global communication, it was not until the start of this century that new areas of investigation were established to understand “the global cultural reality” from other perspectives. Like studies of the book and of publishing, studies of translation began to grow slowly in the mid-1980s but multiplied rapidly from 2000 onward. Today, it is beyond doubt that these areas constitute two of the most stimulating domains for the theoretical renewal of the social sciences and the humanities. Because they are rooted primarily in disciplines such as history and sociology, studies of the book and publishing have not been so greatly affected by the vogues of contemporary theory. This is not the case with translation studies, which has strong links to studies of literature, semiology and the communication sciences. The “actualist fascination” with translation is evidenced by an exaggeration of the virtues of the term itself as a metaphor, as a means of replacing symbols: the expression, in one language, of words written or spoken in another in the strict use or the replacement of one complex sign with another that is more effective for the purposes of comprehension in the broad sense.